Sexual dimorphism in postembryonic development of saffron cod Eleginus gracilis, walleye pollock Gadus chalcogrammus and pacific cod Gadus macrocephalus - О. V. Novikova (Известия ТИНРО, 2025)
Based on the allometric equation of J. Huxley and S. Brody model of body weight, sexual dimorphism and allometric variability between males and females is determined for the first time in postembryonic development of three fish species, using factor and cluster analyses for a set of morphometric parameters. The sexual differences for such parameters as eye diameter, greatest body depth, antedorsal and anteanal distances apper very early and are already evident in juveniles. Females in almost all size-age groups of saffron cod and walleye pollock are ahead of males in the head size, forehead width, antedorsal distance, eye diameter, and body depth. Growth of these species is characterized by alternation of isometry, positive and negative allometry. On the contrary, sexual dimorphism is not revealed for pacific cod that is distinguished by linear growth of all studied plastic features, except the body weight increasing relative to the body length. According to the results of factor analysis, the greatest specific weight in total morphometric variability within age groups and between them was contributed for the studied species by four indices: body length without caudal fin, greatest body depth, eye diameter and forehead width. The cluster analysis allows us to identify general trends in morphophysiological variability of saffron cod and walleye pollock.